Alkali Depolymerization of Poly(ethylene terephthalate) in a Quasi‐solid‐solid Kneading Reaction. Issue 12 (25th October 2021) - Biermann, Lars; Quast, David; Brepohl, Esther; Eichert, Carsten; Scholl, Stephan
Abstract: The alkaline depolymerization reaction of poly(ethylene terephthalate) (PET) under quasi‐solvent‐free conditions was investigated. This is a new approach for recycling PET waste to its monomer building blocks: terephthalic acid and ethylene glycol. The influence of base particle size, reaction temperature, and rotational speed of the employed laboratory kneader on terephthalic acid yield in the quasi‐solid‐solid reaction was investigated. PET is depolymerized almost quantitatively in a reaction time of 5 min at moderate reaction temperatures, with intense mixing affecting the yield of terephthalic acid. The quality of the terephthalic acid monomer, assessed by color index measurements, indicated that the reaction temperature primarily influences the color index of the monomer. By balancing terephthalic acid yield versus color index, optimum reaction conditions were proposed. Abstract : Alkaline depolymerization of poly(ethylene terephthalate) (PET), which is relevant to its recycling, was studied with sodium hydroxide under quasi‐solvent‐free conditions in a laboratory kneader. PET was depolymerized almost quantitatively at moderate temperatures in a residence time of 5 min. The effects of various process parameters on the yield and color index of terephthalic acid were studied.